Glass embedded in labial mucosa for 20 years - Sumanth K; Boaz Karen; Shetty Naresh (Wolters Kluwer Medknow Publications, 2008)
Foreign bodies may be deposited in the oral cavity either by traumatic injury or iatrogenically. Among the commonly encountered iatrogenic foreign bodies are restorative materials like amalgam, obturation materials, broken instruments, needles, etc. Few reports of glass pieces embedded in the soft tissues of the mouth have been published. We report a case where glass pieces had been lodged in the lower labial mucosa for 20 years, with consequent peripheral reactive bone formation.